Introduction to data science with R : manipulating, visualizing, and modeling data with the R language (O'Reilly Media, 2014)
"Learn practical skills for visualizing, transforming, and modeling data in R. This comprehensive video course shows you how to explore and understand data, as well as how to build linear and non-linear models in the R language and environment. It's ideal whether you're a non-programmer with no data science experience, or a data scientist switching to R from other software such as SAS or Excel."--Resource description page.